Use case bellow has obvious typos as missing right hand side values
of equations. Just assume that right hand side of equations bellow has 0
(zerro) values and attempt to create approach to generate matrix with
given values.
In case of values 1-th it is obvious that both diagrams will be updated corespondently and will generate different matrix. Same schema would work
for values sequence 1,0,1,0,1,0,1,0 ..... with another set of fork diagrams.
Assume right hand values are equal 0 (all), otherwise regenerate fork diagrams correspodently
((x1 ^ y1) ~ (x2 ^ y2)) => (x3 ^ y3) = 1
((x2 ^ y2) v ¬(x3 ^ y3)) => (x4 ^ y4) = 1
((x3 ^ y3) ~ (x4 ^ y4)) => (x5 ^ y5) = 1
((x4 ^ y4) v ¬(x5^ y5)) => (x6 ^ y6) = 1
Just repeat. If they are 1-th (on right hand side) or changing 1 with 0 on regular basis, same schema would work as well with corespondently updated fork diagrams. Per right hand side value of first and second equations.
I mean there should be just two diagrams generating matrix.
Each outgoing value of zj having value 0 should mutiply cell's value
content by 3. Here situation is exactly like in P-40 :- zj=xj^yj . Setup with no
changing forking diagrams belongs to Helen Mironchick and may be viewed in ege23.pdf close to top of document
Solution zj = xj^yj
Case "1"
(z1~z2) =>z3 = 1
(z3=>z2) => z4 = 1
(z3~z4) => z5 = 1
(z5=>z4)=>z6 = 1
Case "0"
((x1 ^ y1) ~ (x2 ^ y2)) => (x3 ^ y3) = 0
((x2 ^ y2) v ¬(x3 ^ y3)) => (x4 ^ y4) = 0
((x3 ^ y3) ~ (x4 ^ y4)) => (x5 ^ y5) = 0
((x4 ^ y4) v ¬(x5^ y5)) => (x6 ^ y6) = 0
zj=xj^yj Solution
(z1~z2) =>z3 = 0
(z3=>z2) => z4 = 0
(z3~z4) => z5 = 0
(z5=>z4)=>z6 = 0
In case of values 1-th it is obvious that both diagrams will be updated corespondently and will generate different matrix. Same schema would work
for values sequence 1,0,1,0,1,0,1,0 ..... with another set of fork diagrams.
Assume right hand values are equal 0 (all), otherwise regenerate fork diagrams correspodently
((x1 ^ y1) ~ (x2 ^ y2)) => (x3 ^ y3) = 1
((x2 ^ y2) v ¬(x3 ^ y3)) => (x4 ^ y4) = 1
((x3 ^ y3) ~ (x4 ^ y4)) => (x5 ^ y5) = 1
((x4 ^ y4) v ¬(x5^ y5)) => (x6 ^ y6) = 1
Just repeat. If they are 1-th (on right hand side) or changing 1 with 0 on regular basis, same schema would work as well with corespondently updated fork diagrams. Per right hand side value of first and second equations.
I mean there should be just two diagrams generating matrix.
Each outgoing value of zj having value 0 should mutiply cell's value
content by 3. Here situation is exactly like in P-40 :- zj=xj^yj . Setup with no
changing forking diagrams belongs to Helen Mironchick and may be viewed in ege23.pdf close to top of document
Solution zj = xj^yj
Case "1"
(z1~z2) =>z3 = 1
(z3=>z2) => z4 = 1
(z3~z4) => z5 = 1
(z5=>z4)=>z6 = 1
Case "0"
((x1 ^ y1) ~ (x2 ^ y2)) => (x3 ^ y3) = 0
((x2 ^ y2) v ¬(x3 ^ y3)) => (x4 ^ y4) = 0
((x3 ^ y3) ~ (x4 ^ y4)) => (x5 ^ y5) = 0
((x4 ^ y4) v ¬(x5^ y5)) => (x6 ^ y6) = 0
zj=xj^yj Solution
(z1~z2) =>z3 = 0
(z3=>z2) => z4 = 0
(z3~z4) => z5 = 0
(z5=>z4)=>z6 = 0
No comments:
Post a Comment